2018
DOI: 10.3390/genes9040187
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs and Endometrial Cancer

Abstract: Non-coding RNAs (ncRNAs) are involved in the regulation of cell metabolism and neoplastic transformation. Recent studies have tried to clarify the significance of these information carriers in the genesis and progression of various cancers and their use as biomarkers for the disease; possible targets for the inhibition of growth and invasion by the neoplastic cells have been suggested. The significance of ncRNAs in lung cancer, bladder cancer, kidney cancer, and melanoma has been amply investigated with import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 77 publications
(112 reference statements)
1
53
0
Order By: Relevance
“…Many papers have investigated the role of ncRNA in EC in an attempt to find new molecular markers able to discriminate the different subtypes, predict prognosis and design new drugs for personalized targeted therapies [ 44 , 45 , 46 , 47 ]. In this review, we focused our attention on more important biological pathways and processes altered in EC and we discussed the role of ncRNAs in their regulation.…”
Section: Ncrnas and Endometrial Cancermentioning
confidence: 99%
“…Many papers have investigated the role of ncRNA in EC in an attempt to find new molecular markers able to discriminate the different subtypes, predict prognosis and design new drugs for personalized targeted therapies [ 44 , 45 , 46 , 47 ]. In this review, we focused our attention on more important biological pathways and processes altered in EC and we discussed the role of ncRNAs in their regulation.…”
Section: Ncrnas and Endometrial Cancermentioning
confidence: 99%
“…Zhou et al [44] experimentally con rmed that large intergenic non-coding ribonucleic acid-RoR is a ceRNA and acts as an miR-145 "sponge" to inhibit the mediation of the differentiation of stem cells by miR-145. Vallone et al [45] reviewed the relationship between non-coding RNAs and oncogenesis (lung cancer, bladder cancer, kidney cancer, and melanoma) based on three years of PubMed records.To date, very few ceRNA network studies have been performed with regards to EC. In the present study, correlation analysis showed that CCNE1 in the MEturquiose module was signi cantly negatively correlated with all of the hub genes in the MEbrown module, while all of the hub genes in the MEbrown module were signi cantly positively correlated, indicating that the two modules are not only modules with respect to topology but also with respect to function, and the existence of two modules is reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, mounting evidence has emphasized the roles and clinical significance of non-coding RNAs and, in particular lncRNAs, among others in endometrial cancer (33,34).…”
Section: Discussionmentioning
confidence: 99%